Paradigms - Massimo Lauria; Maria Azzalin (Agathón)
The paper investigates and analyses creation, success and evolution of different Paradigms that have characterised mankind modern history, strongly connecting social, scientific, technological and economic contexts. The paper critically outlines their characteristics, peculiarities and logical structures, and then re-interpret them in the light of the ongoing transition and particularly of the changes that the digital transformation is determining on the important subjects of environmental policies, of technological innovation – and therefore of ‘living’ – and particularly of sustainable building in the digital era. By underlining the success of a new habitat – the digital ecosystem – this reading associates to the mentioned Paradigms, new characteristics outlining attributes, areas, problems and developments of a possible ‘second life’, of which is not quite simple today to foresee results on the architectural languages, the transformations of the implemental procedures, the new characteristic, besides ecological and digital, the ones already known.